2016
DOI: 10.3765/plsa.v1i0.3703
|View full text |Cite
|
Sign up to set email alerts
|

Subject pronoun expression in Mexican Spanish: ¿Qué pasa en Xalapa?

Abstract: Abstract. This study is the first variationist analysis of subject personal pronoun expression (SPE) in the Spanish of Xalapa, Mexico. The overall pronominal rate (25%)-the highest such rate found in Mexican Spanish so far-also constitutes one of the highest in a mainland Spanish variety. Six predictors-four internal and two external-significantly condition SPE. The internal conditioning-congruent with what occurs elsewhere-reveals grammatical number and person of the subject as the strongest predictor. It als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 29 publications
(26 reference statements)
8
21
0
Order By: Relevance
“…Younger and middle-aged speakers slightly disfavoured the use of overt SPs (24%), while older speakers showed a favouring of overt SPs (34%). This finding corroborates previous research that has reported a distinction between younger and older speakers (Orozco & Guy 2008;Carvalho & Child 2011;Alfaraz 2015;Lastra & Martín Butragueño 2015;Orozco 2015Orozco , 2016. This observation in the current data could be an incidental reflection of the differing regional origins of the speakers according to age.…”
Section: Language-internal and Language-external Variablessupporting
confidence: 93%
See 3 more Smart Citations
“…Younger and middle-aged speakers slightly disfavoured the use of overt SPs (24%), while older speakers showed a favouring of overt SPs (34%). This finding corroborates previous research that has reported a distinction between younger and older speakers (Orozco & Guy 2008;Carvalho & Child 2011;Alfaraz 2015;Lastra & Martín Butragueño 2015;Orozco 2015Orozco , 2016. This observation in the current data could be an incidental reflection of the differing regional origins of the speakers according to age.…”
Section: Language-internal and Language-external Variablessupporting
confidence: 93%
“…This distinction between older and younger speakers is generally in line with previous studies (e.g. Orozco & Guy 2008;Carvalho & Child 2011;Alfaraz 2015;Lastra & Martín Butragueño 2015;Orozco 2015Orozco , 2016, including those of other Mexican Spanish varieties (Lastra & Martín Butragueño 2015;Orozco 2016).…”
Section: Social Predictorssupporting
confidence: 90%
See 2 more Smart Citations
“…Since its inception into pronombrismo by Enríquez (1984), the lexical content of the verb classification has been used by many scholars, most notably Zentella (2007, 2012) in their monumental study of SPE in New York City Spanish. The detailed lexical content description provided by Otheguy and Zentella (2012) in their SPE coding manual -a pronombrista guidebook which they generously shared ahead of its publication-prompted many other researchers (Carvalho and Child 2011;Erker and Guy 2012;Flores-Ferrán 2002Orozco 2015aOrozco , 2016Orozco , 2018aOrozco , 2018bOrozco and Guy 2008;among others) to explore the effect of verbs on SPE using this classification. Overall, the lexical content of the verb tendencies tell us that (a) stative verbs favor overt subjects; (b) both mental activity verbs and estimative verbs moderately favor overt subjects-this explains why many studies have examined these two types of verbs jointly (e.g., Erker and Guy 2012; Otheguy and Zentella 2012; Orozco and Guy 2008; among others); and (c) external activity verbs favor null subjects.…”
Section: Lexical Content Of the Verbmentioning
confidence: 99%